MODERASI BERAGAMA SOLUSI HIDUP RUKUN DI INDONESIA - Ida Bagus Alit Arta Wiguna; Ida Ayu Made Yuni Andari (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This research aims to find out the definition and concept of religious moderation, factors that influence religious moderation, the impact of religious moderation, efforts to promote religious moderation and shortcomings and obstacles in implementing religious moderation. This research uses a literature review with qualitative analysis using a critical analysis model. The results of this study are Encouraging interfaith dialogue, Improving multicultural education, encouraging interfaith cooperation, encouraging religious leaders to play an active role in promoting the values of religious moderation and building interfaith cooperation and increasing individual awareness.